Soybean Productivity in Agroforestry Nyamplung (Callophylum inophylum) Pattern in Sandy Soil Coastal Area in Pangandaran, West Java PRODUKTIVITAS KEDELAI PADA POLA AGROFORESTRI NYAMPLUNG (Callophylum inophylum) DI LAHAN PANTAI BERPASIR PANGANDARAN, JABAR - Aditya Hani (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
Coastal land area are potential as a source of fulfillment of food. Environmental conditions in the coastal area generally have a high temperature, saline, sandy soil, strongs winds, and high evaporation. One of the coastal land reclamation method is to use the presence of trees combined with the type of legume crops through agroforestry patterns. This study aims to determine soybean varieties adaptive to the beach area. Experiments using Completely Randomized Design Group. Varieties of soybean in the test consists of four varieties: derings 1 (drought-tolerant), dena 2 (shade tolerant), deram 1 (saline soil tolerant) and local (control). The seeds of each variety were planted in plots measuring 4 x 3 m of 7 replicates. Character of nyamplung plant observed were height and diameter and character of soybean plants observed were: plant height and root length (cm) were taken destructif sampling as many as 10 samples (at 60 days old), number of branches, number of pods, seed weight per plant, seed weight, based weight of 100 grains, and heavy yields. The data were analyzed by using analysis of variance. The results showed that soybean varieties that give the lowest to the highest production is dena (2.37 ton.ha-1), thunder (1.31 ton.ha-1), local (1.13 ton.ha-1) and the ring (0.81 ton.ha-1).Key words : Agroforestry, coastal area, soybean, varieties